Empirical orthogonal function analysis of the interannual variability at 850 hPa of the Northeast monsoon over South East Asia - 388237 Sankaran, Prakash; Quah, Leong Chuan; Malaysia. Kementerian Sains, Teknologi dan Alam Sekitar. Perkhidmatan Kajicuaca (Kuala Lumpur : Perkhidmatan Kajicuaca Malaysia, 1988)
40